Comparative immunophenotyping of peripheral blood lymphocyte subsets in pulmonary tuberculosis and nontuberculous mycobacterial pulmonary disease: a retrospective study - Ren, Shuai; Chen, Ruifang; Xu, Ping; Zhao, Zhangyan; Tang, Haicheng (Frontiers in Immunology, 2025)
ObjectiveTo compare peripheral blood lymphocyte profiles between pulmonary tuberculosis (PTB) and nontuberculous mycobacterial pulmonary disease (NTMPD) patients and explore whether these immunophenotypic differences may assist future diagnostic algorithms.MethodsThis retrospective study analyzed clinical data of 78 PTB patients, 73 NTMPD patients, and 80 healthy controls from the Shanghai Public Health Clinical Center between February 2024 and February 2025. Peripheral blood lymphocyte subsets were measured using flow cytometry. Logistic regression and receiver operating characteristic (ROC) curve analyses were performed to identify and assess diagnostic markers.ResultsNo significant differences in age or body mass index (BMI) were found among the three groups (P > 0.05), but gender distribution differed significantly (P < 0.05). PTB patients had a higher proportion of diabetes mellitus (P < 0.05), while NTMPD patients had a higher prevalence of structural lung disease (P < 0.05). PTB patients also showed higher platelet counts and CD3+, CD4+, and CD45+ lymphocyte counts (gated within the CD45+SSC-Alow population) compared to NTMPD patients (all P < 0.05). ROC analysis indicated that CD4+ lymphocytes had an area under the curve (AUC) of 0.722, with a sensitivity of 65.9% and specificity of 76.7%.ConclusionSignificant differences in peripheral blood lymphocyte subsets exist between PTB and NTMPD patients. The CD4+ counts differed significantly between the two diseases, suggesting that immune profiling could contribute to a broader diagnostic framework once prospectively validated.